T. Butler King of Georgia - Gordon, Matthew (Georgia Open History Library, 1964)
T. Butler King of Georgia documents the life of Georgia politician and planter T. Butler King. Originally from Palmer, Massachusetts, King moved to coastal Georgia, where he got involved with politics and public life. T. Butler King of Georgia explores King's political achievements, including his experience as a Georgia state senator, his promotion of internal improvements, and his appointment as President Zachary Taylor's special agent to California. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.